Perforated Meckel’s Diverticulum: A Case Report - Karina Sudharso, Tea; Angelina Maharani Chandra, Elizabeth; Natalia Sirait, Anike (Green Publisher Indonesia, 2024)
Meckel’s diverticulum is a true diverticulum that consists of all layers of bowel normally found in a normal small bowel wall. The three most common presentations in children are intestinal bleeding (30–56%), intestinal obstruction (14–42%), and diverticular inflammation (6–14%). Complications result in more severe symptoms, such as acute abdomen and signs of peritonitis. These presentations are not specific to Meckel’s diverticulum and can be found in many other conditions, making the diagnosis difficult. A five-year-old child came to the emergency department with complaint of acute abdominal pain, especially in the right lower quadrant. The pain was accompanied by vomiting. On physical examination, patient was febrile and signs of peritonitis were found. Abdominal plain film revealed the probability of focal inflammation in the right lower region of the abdomen, with partial intestinal obstruction. Ultrasonography showed a presence of a mass in right iliac region with the size of 24x20x23 mm, with normal appendix. During exploratory laparotomy, a necrotic and perforated Meckel’s diverticulum was found, with associated purulent matter. Diverticulectomy with segmental resection of ileum followed by end-to-end anastomosis were done. Diagnosis of Meckel’s diverticulum requires a high index of suspicion, especially in the pediatric population. It is important for clinicians to be aware of unusual presentations of Meckel’s diverticulum.